L-Fuzzy Prime Spectrums of ADLs - Natnael Teshale Amare; Srikanya Gonnabhaktula; Ch. Santhi Sundar Raj (Advances in Fuzzy Systems)
The notion of an Almost Distributive Lattice (ADL) is a common abstraction of several lattice theoretic and ring theoretic generalizations of Boolean algebra and Boolean rings. In this paper, the set of all L-fuzzy prime ideals of an ADL with truth values in a complete lattice L satisfying the infinite meet distributive law is topologized and the resulting space is discussed.